Candlestick charting / by Larissa J. Adamiec, PhD, and Russell Rhoads, PhD. - Adamiec, Larissa J.; Rhoads, Russell (--For dummies., 2026)
Candlestick Charting For Dummies explains how to read the market's story and act on it with precision and confidence before anyone else. It's perfect for beginning traders, as well as those with a little bit of experience under their belts who want to brush up on their skills and check out the latest trading strategy updates